Teacher training for the construction of Digital Educational Games: a systematic literature review (Research, Society and Development, 2021)
Considering the changes that have occurred in the school over the years, caused by the insertion of digital technologies in the educational context, our teachers have increasingly demanded new skills and competences to work with current 21st century learners. Among all the technologies that we can find each day even more present in the school environment, one that has been standing out in the context of education is the use of digital games, especially those produced for educational purposes. However, as digital games show themselves as a new proposal for teachers to work with students, the question arises regarding the offer of a specific teacher training that aims to prepare these teachers not only for use as also for the construction of these new digital educational resources, considering that these are the professionals who know the pedagogical contents and practices, as well as the reality of the school and students. Therefore, this work seeks to present a Systematic Literature Review that sought to investigate the existence of scientific papers, published between January 2015 and April 2021, about the provision of training for educators for the construction of digital educational games. For the construction of the review, we adopted the steps of planning, conducting and reporting presented in the article's methodology. Thus, it is emphasized that the studies found throughout the review were carefully analyzed and the results found were synthesized throughout this work.